Hypoxia upregulates neutrophil degranulation and potential for tissue injury. Issue 11 (31st August 2016) - Hoenderdos, Kim; Lodge, Katharine M; Hirst, Robert A; Chen, Cheng; Palazzo, Stefano G C; Emerenciana, Annette; Summers, Charlotte; Angyal, Adri; Porter, Linsey; Juss, Jatinder K; O'Callaghan, Christopher; Chilvers, Edwin R; et al.
Abstract : Background: The inflamed bronchial mucosal surface is a profoundly hypoxic environment. Neutrophilic airway inflammation and neutrophil-derived proteases have been linked to disease progression in conditions such as COPD and cystic fibrosis, but the effects of hypoxia on potentially harmful neutrophil functional responses such as degranulation are unknown. Methods and results: Following exposure to hypoxia (0.8% oxygen, 3 kPa for 4 h), neutrophils stimulated with inflammatory agonists (granulocyte-macrophage colony stimulating factor or platelet-activating factor and formylated peptide) displayed a markedly augmented (twofold to sixfold) release of azurophilic (neutrophil elastase, myeloperoxidase), specific (lactoferrin) and gelatinase (matrix metalloproteinase-9) granule contents. Neutrophil supernatants derived under hypoxic but not normoxic conditions induced extensive airway epithelial cell detachment and death, which was prevented by coincubation with the antiprotease α-1 antitrypsin; both normoxic and hypoxic supernatants impaired ciliary function. Surprisingly, the hypoxic upregulation of neutrophil degranulation was not dependent on hypoxia-inducible factor (HIF), nor was it fully reversed by inhibition of phospholipase C signalling. Hypoxia augmented the resting and cytokine-stimulated phosphorylation of AKT, and inhibition of phosphoinositide 3-kinase (PI3K)γ (but not other PI3K isoforms) prevented the hypoxic upregulation of neutrophil elastase release. Conclusion: Hypoxia augments neutrophil degranulation and confers enhanced potential for damage to respiratory airway epithelial cells in a HIF-independent but PI3Kγ-dependent fashion.